An annotated checklist of ichthyofauna and associated estuarine biota of the Manakudy Estuary, southern Tamil Nadu, India - Adyasha Sahu; Jayakumar Natarajan; Sudhan Chandran; Durairaja Ramulu; P. Padmavathy; P. Velmurugan; Domendra Dhruve; Debabrata Panda; Kamei Ringjonmeilu; Narsingh Kashyap (Journal of Fisheries, 2026)
This study assessed the ichthyofaunal and associated floral diversity of the Manakudy Estuary, southwest coast of India, over a two-year period involving monthly surveys from August 2023 to July 2025. Sampling efforts were stratified across three distinct ecological zones i.e., freshwater influx region (Station 1), mid-mangrove area (Station 2), and estuarine mouth region (Station 3), utilizing traditional fishing crafts and standardized visual census methods to capture spatial heterogeneity. A total of 120 species were recorded, representing 37 orders, 62 families, and 89 genera. The order Eupercaria incertae sedis showed the highest species richness (15.83%), followed by Carangiformes (12.50%) and Clupeiformes (8.33%). Among families, Carangidae was the most dominant with 13 species. Conservation assessment revealed the occurrence of threatened species, including the Endangered honeycomb stingray (Himantura uarnak) and the Vulnerable Coromandel whipray (Brevitrygon imbricata), along with two near threatened species. These findings provide baseline information essential for long-term biodiversity monitoring, sustainable fisheries management, and conservation planning in the Manakudy Estuary.